Cotton Sector Strategies in West and Central Africa - Badiane, Ousmane (World Bank, Washington, DC, 2014)
Cotton production is truly a success story in West and Central Africa. The region is now the second largest exporter of lint, after the United States, with a world market share of 15 percent. Despite its strong performance in the past, the sector is characterized by several institutional and structural weaknesses that jeopardize its viability in an era of increasing globalization of the cotton industry. The sector's future performance will also depend on the implications of cotton sector policies in major producing countries such as the United States, the European Union, and China. This paper examines how the above factors may affect future growth of the region's cotton industry. It also identifies the changes that are required to enable countries in the region to fully exploit the sector's significant growth potential.